Causal Impotence and Evolutionary Influence: Epistemological Challenges for Non-Naturalism - Crow, Daniel (Ethical theory and moral practice, 2016)
Two epistemological critiques of non-naturalism are not always carefully distinguished. According to the Causal Objection, the fact that moral properties cannot cause our moral beliefs implies that it would be a coincidence if many of them were true. According to the Evolutionary Objection, the fact that evolutionary pressures have influenced our moral beliefs implies a similar coincidence. After distinguishing these epistemological critiques, I provide an extensive defense of the Causal Objection that also strengthens the Evolutionary Objection. In particular, I formulate a Master Causal Objection featuring the controversial premise that non-naturalism can provide no adequate explanation for moral knowledge. I defend this premise by first narrowing down the range of candidate explanations to conceptual, constitutive, and evolutionary explanations, and then considering and eliminating each of these in turn. My discussion of evolutionary explanations suggests that non-naturalists must refute the Causal Objection in order to refute the Evolutionary Objection.